2022
DOI: 10.1155/2022/7095467
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Management of Skeletal Class II Malocclusion with the Invisalign Mandibular Advancement Feature Appliance: A Case Report and Review of the Literature

Abstract: The treatment of Class II malocclusion due to mandibular retrognathia is one of the most common challenges met in orthodontic practice. When it comes to a growing patient, functional appliances are the optimal way to achieve growth modification by enhancing mandibular growth. Clear aligners have been part of the orthodontic treatment for several decades but until recently they were only used to correct mild malocclusions. In 2017, Align Technology introduced the Invisalign with Mandibular Advancement Feature (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Compared with traditional appliances, MA has good aesthetics, high wearing comfort, higher accuracy and can complete orthopedic and orthodontic treatment at the same time. MA appears to be effective in the treatment of class II malocclusions with mandibular retrusion [7][8][9]. Like functional appliances, the correction of occlusion relationships is combined skeletal and dental effects, and Sabouni et.al found that the skeletal changes may be minor [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with traditional appliances, MA has good aesthetics, high wearing comfort, higher accuracy and can complete orthopedic and orthodontic treatment at the same time. MA appears to be effective in the treatment of class II malocclusions with mandibular retrusion [7][8][9]. Like functional appliances, the correction of occlusion relationships is combined skeletal and dental effects, and Sabouni et.al found that the skeletal changes may be minor [10].…”
Section: Introductionmentioning
confidence: 99%
“…, all variables except movement of maxillary osseous base were statistically different. Linear changes measured along the mean functional occlusal plane during treatment are depicted diagrammatically in the pitchforks (Fig 3,4,5,6,7,8,9,10,11)…”
mentioning
confidence: 99%
“…To correct this condition and allow for a favorable tooth position to perform the MA phase with precision wings, two sets of aligners were required, considering the growth potential inherent in the hypodivergent facial biotype. Usually, one set of aligners would be enough, but the biological component of the impacted pre-molar made it necessary to carry out two sets [ 9 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This can be explained by the fact that the child has a marked loss of the occlusion vertical dimension, with the anterior rotation of the mandible aggravated by the protruded chin. This situation promotes a very concave profile, which, in addition to being considered unsightly, is a typical aged profile [ 9 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional braces make precise wire adjustments within 0.5 mm to intrude or extrude teeth as necessary, making them highly efficient in different cases. Although these two articles conclude that clear aligners should be used in simple malocclusions, 26 studies conducted by Koukou et al concluded that clear aligners effectively treat all class malocclusions 27 . While traditional braces can treat more severe malocclusions because of their strength, control, and precisely adjustable wiring, one article claims that clear aligners have been frequently applied in these situations in orthodontic clinic practices.…”
Section: Figure 1: Obtained From British Journal Of Orthodontics 1974mentioning
confidence: 99%